2017 International Symposium on Computers in Education (SIIE) 2017
DOI: 10.1109/siie.2017.8259664
|View full text |Cite
|
Sign up to set email alerts
|

Trends in online consumption and sharing of content by higher education students

Abstract: Abstract-This article presents a literature review about media consumption and content sharing on the Internet and is part of a research project that aims to outline and understand practices shared among students of a specific Portuguese higher education institution. Much of the studies found allow us to conclude that students that currently attend higher education are used to multitasking and are active users of online devices, platforms and services in both personal and learning contexts. Research shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Gen Y or millennials (defined as those born between 1981 and 1990) stay connected online and multitask through technology, spend considerable time consuming content, sharing, contributing, and participating in on-line communities with high intensity. A recent survey showed that 80% of millennials perform daily on-line social networking and information search activities (Moráis et al, 2017). Millennials also exhibit the social dilemma for on-line sharing.…”
Section: Survey Design and Administrationmentioning
confidence: 99%
“…Gen Y or millennials (defined as those born between 1981 and 1990) stay connected online and multitask through technology, spend considerable time consuming content, sharing, contributing, and participating in on-line communities with high intensity. A recent survey showed that 80% of millennials perform daily on-line social networking and information search activities (Moráis et al, 2017). Millennials also exhibit the social dilemma for on-line sharing.…”
Section: Survey Design and Administrationmentioning
confidence: 99%
“…This research explores the implications of these digital shifts for pedagogical strategies and the integration of technology into curricular design. In this digital era, information is not only passively received but also generated and shared by students (Morais et al, 2017). This requires a new approach in education that emphasizes the importance of digital literacy and critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%